X+5y=21
x+3y=11
3x+y=13
5x+2y=7
x+5y=21
x+3y=11
x=21-5y (isolate x)
sub the value of x to 2nd equation to solve for y
21-5y+3y=11
-2y=-10
y=5
substitute the value of y into the other equation to solve for x
x+5(5)=21
x+25=21
x=-4
Do you see what I did? Now follow the same method for solving the second one and show me what you get
from this
1x + 5y = 21
1x + 3y = 11
1 5
1 3
1*3 - 1*5 = 3-5 = -2
the determinant of the equation
Then find the determinant of a replacement:
replace the constants of the variable x:
21 5
11 3
21*3 - 11-5 = 63 - 55 = 8
Then divide this determinant with the system determinant:
8 / -2 = -4
Thus x = -4
Then do the same and replace the constant of y:
1 21
1 11
1*11 - 21*1 = 11 - 21 = -10
-10 / -4 = 2.5
thus y = 2.5